2013
DOI: 10.1038/gt.2013.68
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral gene therapy versus intravenous gene therapy for distant metastasis control with 2-Diethylaminoethyl-Dextran Methyl Methacrylate Copolymer Non-Viral Vector–p53

Abstract: Lung cancer still remains to be challenged by novel treatment modalities. Novel locally targeted routes of administration are a methodology to enhance treatment and reduce side effects. Intratumoral gene therapy is a method for local treatment and could be used either in early-stage lung cancer before surgery or at advanced stages as palliative care. Novel non-viral vectors are also in demand for efficient gene transfection to target local cancer tissue and at the same time protect the normal tissue. In the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9] Potential advantages of IT delivery of anticancer drugs include better anticancer effectiveness through achievement of high concentrations of anticancer agents within the tumor microenvironment and reduced systemic adverse drug reactions (ADRs) and drug resistance. 5,[10][11][12] In general, single-agent efficacy has been less than satisfying to date; however, promising results have been achieved using IT-administered targeted therapies, combined with conventional chemotherapy or radiation. 10,[13][14][15][16][17] A major challenge of cancer therapy is immune resistance orchestrated by the tumor microenvironment, which promotes tumor survival.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Potential advantages of IT delivery of anticancer drugs include better anticancer effectiveness through achievement of high concentrations of anticancer agents within the tumor microenvironment and reduced systemic adverse drug reactions (ADRs) and drug resistance. 5,[10][11][12] In general, single-agent efficacy has been less than satisfying to date; however, promising results have been achieved using IT-administered targeted therapies, combined with conventional chemotherapy or radiation. 10,[13][14][15][16][17] A major challenge of cancer therapy is immune resistance orchestrated by the tumor microenvironment, which promotes tumor survival.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported recently that the administration of DDMC as an aerosol [25] and the use of DDMC/p53 in intratumoral gene therapy [26] were effective. DDMC is very suitable for experiments using targeted siRNA or miRNA transfection in vivo.…”
Section: Reviewmentioning
confidence: 99%
“…The resulting DDMC consists of "hairy" nanoparticles having a hydrophilic-hydrophobic microseparated domain with an amphiphilic domain (DEAE-dextran) and a hydrophobic domain (PMMA) that form a polymer micelle [15]. It has been reported that DDMC is superior to other transfection agents with safety efficacy by autoclaved as a non-viral carrier for gene introduction [16][17][18][19][20][21][22][23][24]. On the other hand, the paclitaxel is well known as a strong anti-cancer drug to introduce cancer cells to apoptosis in stabilization of tubulin (i.e., tubulin polymerization) [14,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%